Politics, Literature, Folklore and Circumnavigating the World: The What, Why and How of Digital Collections at Curtin University Library - Haddow, Gaby; Wallace, Lesley (ALIA, 2008)
This paper explores the journey Curtin University Library has taken in providing digital access to recently acquired collections. It discusses the collections, outlines important criteria and processes, and presents the challenges and benefits of digitising collections.Building on the expertise gained in establishing the digital archive of the John Curtin Prime Ministerial Library, Curtin University Library has since developed a number of digital collections with themes as varied as politics, literature, folklore and circumnavigating the world.In order to consider collections of vastly different subject matter, formats and information types for acceptance, the Library developed ?Archival Collections Principles? and a selection checklist for donations. These documents ensure decisions are made in a consistent and defensible manner, and take into account available resources. The range of formats (e.g. print, audio, video, images, objects) and information types (e.g. speeches, scrapbooks, journal articles, plays, sail plans, echo sound charts, questionnaires, interviews) across the collections has required an individual and creative approach to organising and providing digital access to each collection.The benefits resulting from these activities include utilising and developing staff expertise, making valuable collections widely available where they otherwise would have remained largely inaccessible, and enhancing the reputation of Curtin University.For libraries considering developing a digital collection, this paper outlines some useful principles and guidelines with which to proceed.